Adipokines as metabolic modulators of ovarian functions in livestock: A mini-review - Bharati, Jaya; Bharti, Mukesh Kumar; Kar, Debasish; Sahoo, Pravas Ranjan (Journal of Advanced Veterinary and Animal Research, 2016)
Adipose tissue is the principal fat storing tissue which secretes various molecules known as adipokines. The major adipokines secreted from adipose tissue are leptin, adiponectin, visfatin, resistin, chemerin and apelin. Adipokines are regarded as the "marker of body metabolic status" which maintains the body energy homeostasis. An adequate energy level is essential for the onset of puberty and ovarian functions. Adipokines act as energy sensor and signal the body energy level to hypothalamic neurons to regulate many physiological activities including ovarian functions such as onset of puberty, estrus behavior, follicular development and ovulation followed by corpus luteum (CL) formation and function in livestock. However, adipose tissue dysfunctions limit adipokines secretion leading to an imbalance in body energy level which ultimately affects the reproduction in livestock. This mini-review highlights the modulatory roles of various adipokines in ovarian functions of livestock. http://doi.org/10.5455/javar.2016.c158